1984
DOI: 10.1128/aem.47.2.335-337.1984
|View full text |Cite
|
Sign up to set email alerts
|

Virus movement in soil during saturated and unsaturated flow

Abstract: Virus movement in soil during saturated and unsaturated flow was compared by adding poliovirus to sewage water and applying the water at different rates to a 250-cm-long soil column equipped with ceramic samplers at different depths. Movement of viruses during unsaturated flow of sewage through soil columns was much less than during saturated flow. Viruses did not move below the 40-cm level when sewage water was applied at less than the maximum infiltration rate; virus penetration in columns flooded with sewag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“… Bitton et al [1984] and Jorgensen [1985] postulated that the increased retention of viruses under unsaturated conditions is promoted by the closer proximity of the viruses to the solid surfaces. Lance and Gerba [1984] and Chu et al [2001], however, have suggested that increased attachment of viruses to the SWI is due to a more pronounced effect of electrostatic and hydrophobic interactions under unsaturated conditions, as larger pores are no longer available for transport and viruses are closer to the SWI. We believe that this is unlikely to be the reason, as was also dismissed by Powelson et al [1990], because the effective range of these forces is in the order of nanometers and the sizes of water‐filled pores is much larger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Bitton et al [1984] and Jorgensen [1985] postulated that the increased retention of viruses under unsaturated conditions is promoted by the closer proximity of the viruses to the solid surfaces. Lance and Gerba [1984] and Chu et al [2001], however, have suggested that increased attachment of viruses to the SWI is due to a more pronounced effect of electrostatic and hydrophobic interactions under unsaturated conditions, as larger pores are no longer available for transport and viruses are closer to the SWI. We believe that this is unlikely to be the reason, as was also dismissed by Powelson et al [1990], because the effective range of these forces is in the order of nanometers and the sizes of water‐filled pores is much larger.…”
Section: Resultsmentioning
confidence: 99%
“…Under unsaturated conditions, viruses are believed to be present mainly in the water phase, on the AWI, and on the SWI. Virus transport in the unsaturated zone is greatly influenced by degree of water saturation [ Chu et al , 2001; Jin et al , 2000; Lance and Gerba , 1984; Powelson et al , 1990; Poletika et al , 1995]. The AWI is believed to be a site of strong adsorption for both hydrophobic and hydrophilic colloidal particles.…”
Section: Introductionmentioning
confidence: 99%
“…In general, viruses as well as other colloids have to move through the vadose zone before they can reach groundwater. Overall, the transport mechanisms of colloids in saturated porous media have been studied in great detail in various aspects [e.g., Small , 1974; Lance and Gerba , 1984; McDowellboyer et al , 1986; Bales et al , 1989; Corapcioglu and Jiang , 1993; Sim and Chrysikopoulos , 1996; Chrysikopoulos and Sim , 1996; Rehmann et al , 1999; Bradford et al , 2002; Sirivithayapakorn and Keller , 2003]. However, the mechanisms of colloid transport in the unsaturated porous media needed to be understood in greater detail, since there are some significant differences.…”
Section: Introductionmentioning
confidence: 99%
“…[5] For colloid transport in the unsaturated zone, colloids are believed to be present mainly in the water phase, the air-water interface (AWI), and the solid-water interface (SWI). The transport of colloids in the unsaturated zone is thus greatly influenced by water content [Vilker and Burge, 1980;Lance and Gerba, 1984;Powelson et al, 1990;Poletika et al, 1995]. The AWI has high affinity for both hydrophobic and hydrophilic colloids and the sorption of colloids onto the AWI is often considered almost irreversible under unsaturated conditions, due to the capillary forces that hold the colloids at the interface [Ducker et al, 1994;Wan et al, 1994;Wan and Wilson, 1994b;Wan and Tokunaga, 2002;Costanza-Robinson and Brusseau, 2002;Sirivithayapakorn and Keller, 2003].…”
Section: Introductionmentioning
confidence: 99%